EVALUASI PEMANFAATAN PENGGUNAAN LAHAN BERBASIS POLA RUANG KAWASAN BUDIDAYA KABUPATEN HULU SUNGAI UTARA - Budi Susilo; Gusti Muhammad Hatta; Badaruddin Badaruddin; Syarifuddin Kadir (EnviroScienteae, 2019)
Regency in addition to the limited availability of land is the presence of overlapping of Cultivation Area land use. The purpose of this study was to evaluate and assess the suitability of land use for the Spatial Patterns of Cultivation Areas of Spatial Plan and to provide policy direction in the land use utilization process. To achieve these objectives, a spatial approach was carried out. Spatial analysis was carried out by overlaying the actual land use map with the Spatial Patterns of Cultivation Areas of Spatial Plan. The next step was to evaluate the suitability of land use in Hulu Sungai Utara Regency in order to assess the suitability of the actual land use utilization of the predefined Spatial Patterns of Cultivation Areas of Spatial Plan. The results of the analysis showed that there were actual unplanned land uses in the Cultivation Area Pattern due to changes in the regional administrative boundary of 786.48 ha. Regarding the suitability of land use utilization to the Spatial Patterns of Cultivation Areas, forms of inconsistency were found. The evaluation results showed that the level of inconsistency in land use utilization in Hulu Sungai Utara Regency was in the low inconsistency category (24.68%). The policy directives in utilizing land use were controlling utilization of space, reviewing, and revising the Plan of Spatial Patterns of Cultivation Areas for Hulu Sungai Utara Regency.